The Racial and Ethnic Composition and Distribution of Primary Care Physicians - Xierali, Imam M. (J Health Care Poor Underserved, 2018)
Racial and ethnic minority physicians are more likely to practice primary care and serve in underserved communities. However, there are micro-practice patterns within primary care specialties that are not well understood. To examine the differences among primary care physician practice locations by specialty and race/ethnicity, a retrospective study was conducted on U.S. medical graduates who were direct patient care physicians in 2012. The group-specific contributions to primary care accessibility were decomposed by individual group of minorities underrepresented in medicine (URM). Results confirm significant differences not only in their distribution across underserved areas but also in their racial/ethnic composition by primary care specialties, with internist most diverse and family physicians least diverse. However, stratified analysis shows that within each primary care subspecialty, URM physicians were more likely to practice in underserved areas than their White peers regardless of specific specialties.